The dilemmas and countermeasures of postgraduate management from the perspective of oriental management - Hu, Jun (Frontiers in Psychology, 2026)
Postgraduate education provides technological and talent support for the growth of China’s high-quality economic. Scientific and rational management is an important way to ensure the quality of postgraduate education. There are some dilemmas by traditional hierarchical management model for postgraduates. This study investigates the countermeasures from the perspective of Oriental Management. It can innovate the postgraduate management philosophy by applying the “Five Behaviors” of Oriental Management (i.e., humanistic behavior, psychology behavior, relationship behavior, strategy behavior and human resource behavior).